Position of Patients with Mid-Range Ejection Fraction in the General Chronic Heart Failure Population - N. T. Vatutin; A. N. Shevelok; V. V. Venzheha (Архивъ внутренней медицины)
The European society of cardiology guideline for the diagnosis and treatment of acute and chronic heart failure (CHF) in 2016 identified a new group of patients with mid-range left ventricular ejection fraction (LVEF) with reference interval in the range of 40-49 %. This review highlights the issues of epidemiology and etiology of CHF, outlines the echocardiographic portrait, biomarker profile and patients` dynamic phenotypes, considers the guidelines of their managements and the prognosis of the disease determiner’s factors. Special attention is paid to the peculiarities of the formation of this heterogeneous cohort of patients and the feasibility of expanding the existing CHF classification by introducing two transitional phenotypes.